2019
DOI: 10.1136/bmjophth-2019-000295
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of IgG4-related ophthalmic disease after debulking surgery: a single-centre retrospective study

Abstract: ObjectiveThis study aimed to examine the natural course and relapse rate of IgG4-related ophthalmic disease (IgG4-ROD) after debulking surgery in Japanese patients.Methods and analysisThis retrospective review included patients with IgG4-ROD who did not undergo further treatment following debulking surgery. The patients were diagnosed between January 2009 and December 2018 at the Department of Ophthalmology and Pathology, Niigata University Medical and Dental Hospital. The main outcome measures included postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
1
4
0
2
Order By: Relevance
“…Tacelli et al revealed that maintenance steroid therapy lasting longer than 1 year could reduce the risk of relapse [ 24 ]. Surgical treatment as an alternative treatment for IgG-ROD has been shown to have a lower relapse rate than glucocorticoid therapy [ 25 ]. All the IgG4-ROD patients in our cohort had a relapse rate of 38.9%, and in particular, those in the short-duration group had a relapse rate of 26.9%; these findings confirmed the results of previous studies, suggesting that surgical treatment for IgG4-ROD likely has a lower relapse rate than glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tacelli et al revealed that maintenance steroid therapy lasting longer than 1 year could reduce the risk of relapse [ 24 ]. Surgical treatment as an alternative treatment for IgG-ROD has been shown to have a lower relapse rate than glucocorticoid therapy [ 25 ]. All the IgG4-ROD patients in our cohort had a relapse rate of 38.9%, and in particular, those in the short-duration group had a relapse rate of 26.9%; these findings confirmed the results of previous studies, suggesting that surgical treatment for IgG4-ROD likely has a lower relapse rate than glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ominato et al 13 reported a case series of patients with IgG-ROD treated solely with surgical debulking. The results showed that debulking surgery could be a treatment option for IgG4-ROD.…”
Section: Discussionmentioning
confidence: 99%
“…Ominato et al [ 13 ], in 2019, also reported that debulking surgery might be an effective treatment for IgG4-dacryoadenitis with a relapse rate of 13.3%, which is much lower than the reported relapse rate (26–50%) of the prednisolone therapy. However, compared with the cases in the Ominato et al [ 13 ] study, our case was more complicated with not only the lacrimal gland involvement but also involvement of the right eyelid and bilateral supraorbital nerves. Moreover, baseline elevations of the value of serum IgG4 (1970 mg/dL) and eosinophilia are strongly associated with the greater risk of subsequent relapse [ 7 ].…”
Section: Discussionmentioning
confidence: 99%